Oxidation of cobalt(ii) bispidine complexes with dioxygen* - Comba, Peter; Pokrandt, Bianca; Wadepohl, Hubert (Australian journal of chemistry, 2017)
Bispidine (3,7-diazabicyclo[3.3.1]nonane) ligands, derivatives of diazaadamantane, possess a very rigid backbone and have a high degree of pre-organization for cis-octahedral coordination geometries. Despite their rigidity, they exert a flexible coordination sphere, resulting in stable complexes with a variety of metal ions in various oxidation states. Due to the known high III/II redox potentials of their cobalt complexes, the CoII bispidine complexes are generally resistant to oxidation by dioxygen. Discussed in the present study are various CoII bispidine complexes with tetra- and pentadentate bispidines, with one of these complexes shown to be unstable under aerobic conditions. The decay process has been identified as an oxidative elimination of the 2-methylene pyridine substituent at one of the tertiary amine donors, resulting in picolinate, which is found coordinated to a CoIII product, where the dealkylated N-donor remains unprotonated. The mechanism of this interesting reaction has been studied, and details of the resulting structure of the product complex are discussed.
Gesehen am 28.08.2018